The Analysis of Nurse Performance During Covid-19 Pandemic: A Case Study from Private Hospital in Tangerang - Retna Yulianti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
The performance of nurses as the front line is crucial in handling covid 19. The purpose of the research was to determine the effect of employee training, employee engagement, and work motivation on nurse performance in the healthcare industry when the COVID-19 pandemic occurred. The object of this research is a nurse with a staff position and a coordinator who works at the AN-NISA hospital located in Tangerang with 140 respondents from February until March 2021. This research uses a quantitative approach which will use questionnaire measuring tools and employee performance data during 2020. Data analysis using path analysis. This research concluded that appropriate employee training, employee engagement, and work motivation had a significant effect on nurse performance. However, employee training and work motivation have no significant effect on nurse performance through employee engagement when the COVID-19 pandemic occurred.